Contribution of variable gauge freight wheelsets to interoperability. (May 2019) - Kaiser, I; Vinolas, J; Gómez del Pulgar, D; Galán, R
Railway running gear with variable gauge has been successfully introduced in vehicles for passenger traffic providing a drastic reduction of the time required for the gauge change. Therefore, using wheelsets with variable gauge even for freight wagons seems to be a very promising option for accelerating freight traffic. However, there are several concerns regarding the higher mass of such wheelsets, which increase the unsprung mass of the vehicle with an effect on the dynamics. In order to assess these concerns, the running behaviour of a freight wagon on a straight track and in a curve and its risk of rolling contact fatigue are compared for different configurations of the vehicle; these configurations are determined by the inertia of the wheelsets, by the track geometry using the standard and the Iberian gauge, by the wheel profile and by the loading condition. The comparison of the results shows that the higher inertia of the variable gauge wheelset does not cause drastic changes in the running behaviour. Therefore, with regard to the dynamic behaviour, the use of variable gauge wheelsets in freight wagons is a feasible solution.